Literasi Dakwah Digital pada Akun Media Sosial Instagram Nahdlatul Ulama @nuonline_id - Zulfikar Ikrom; Muhammad Fauzan Nugraha (Universitas Islam Negeri Madura, 2024)
This research aims to analyze digital da'wah literacy carried out by the Instagram account @nuonline_id. Using descriptive qualitative methods and agenda setting theory, this research examines how these accounts utilize social media platforms to spread Islamic messages. The research results show that the @nuonline_id account has succeeded in reaching 1.1 million followers and presents a variety of preaching content, ranging from quotes from Al-Qur'an verses and hadith to the latest news and health information. This content is packaged creatively and innovatively, utilizing Instagram features to attract the attention of the audience. This research concludes that digital da'wah literacy carried out by @nuonline_id is quite effective in spreading Islamic messages and reaching a wide audience.